Problematika Hukum Penerapan Presidential Threshold dalam Pemilihan Umum di Indonesia - Asep Wijaya; Rosmini; Poppilea Erwinta (Fakultas Hukum Universitas Mulawarman, 2020)
Presidential Threshold is a problem because the dynamics of politics is dynamic. The number of votes gained by a political party in the last general elections will likely get the same number of votes at the time of the general elections. Moreover, the urgency of the diatity of this condition then reduce the right of everyone to get the same opportunity in the Government. Threshold of presidential nominations including open legal policy due to the source of attribution authority in the Constitution, especially in article 6A paragraph (2) and article 22E paragraph (6) of the Republic of the State law Indonesia year 1945 as a higher legal norm does not regulate or give limits to anyone who wants to run for presidential candidate and vice president. Keywords: constitution, general election, submission of candidate pair, threshold